Journey towards hope with hope: An interpretative phenomenological analysis of Maldivian mothers raising children with autism / Farzana Shaugee - Farzana , Shaugee (2017)
Autism is a lifelong developmental disorder. The role of the main caregiver, in particular, the mother is critical in the treatment process. A phenomenological study was conducted to get an in-depth understanding of the experience of Maldivian mothers raising children with autism. A purposive sample was selected among Maldivian mothers who have been raising a child diagnosed with autism. The mothers selected were those who have at some point in their children’s life been in contact with the speech pathologist and therapist. In-depth interviews were conducted with six Maldivian mothers raising children with autism. There were four core findings of the research that has implications for clinicians who work with children with autism. First, the mother’s ‘maternal intuitive diagnosis’, sensing of differences in their children’s development at a very young age. Second, the pattern of the grieving process that all mothers go through when their children are diagnosed with autism as well simultaneously going through the treatment process like a ‘warrior’. Third, the mother’s acceptance of one’s child having a long-term disability such as autism as one’s destiny in a faith-based positive way. Fourth, ways in which the mothers go through a process of ‘maternal metamorphosis, a transformative process in which the mothers change and adapt their self in order to take care of their autistic children. This research will be beneficial to clinicians treating children with autism or any such long-term disability with implications that the findings can be used by the clinicians in formulating a better process of diagnosis, counselling, treating and empowering the mothers (caregivers) through their journey of raising their autistic children.